Implementation of Positive Advanced Recovery Connections in Primary and Secondary Mental Health Care—A Registered Advanced Nurse Practitioner‐Led Initiative. - Cunningham, A.; De La Harpe Golden, D.; Pink, M.; Truszkowska, E.; Byrne, T.; Murphy, C.; Strahann, A.; Doyle, C.; Kasemiire, A.; Frawley, T. (Journal of Advanced Nursing (John Wiley & Sons, Inc.), 2025)
Aim(s): This study reports on the implementation of a registered advanced nurse practitioner intervention. Aims include improving access, service user outcomes and integration between primary and secondary care. Design: This paper reports the quantitative results of a mixed methods implementation study. Qualitative data are reported separately. The PARiHS framework informs the implementation process itself, with considerations for nurses and other healthcare professionals explored. Methods: The CORE‐OM 34 item rating scale was administered both pre‐ and post‐intervention. Service user attendances in secondary care was monitored. Results: Findings suggest that the intervention was associated with clinically significant improvements in global or generic distress, reported by service users, as evidenced by changes in the CORE‐OM scores. Access to care was recorded at an average of 3.6 days. Implementation science supported effective and safe implementation with clear governance structures. Conclusion: Registered advanced nurse practice in mental health clinics which provide full episodes of care results in improved integration and may be associated with positive patient outcomes. Implementation science is taught on Irish nursing programmes and this is important if innovative services are to be embedded in the healthcare system. Impact: The development of a model of care for mental health Registered Advanced Nurse Practitioners at the interface of primary and secondary care settings may be merited. Positive Advanced Recovery Connections may be associated with improving mental health outcomes and bolstering integration of primary and secondary care services. The utilisation of implementation science highlights the need for collaboration with all stakeholders to overcome barriers and recognise facilitators to attain the necessary model of integrated care. Patient and Public Contribution: Peer recovery input was provided by members of the service Recovery College, with participation evident in all stages of the project. The psychosocial assessment template was also co‐designed.